2011
DOI: 10.1111/j.1471-0307.2011.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

A modelling study on kefir grain biomass growth: Influence of various minerals

Abstract: In this study, the effect of initial kefir grain concentration and various minerals (MgO, MgSO4.7H2O, ZnSO4.7H2O, CaSO4.1/2H2O and Fe2O3) on the propagation of kefir grains and the pH evolution of kefir were investigated. The activated kefir grains were inoculated into very low fat (0.1%) cows’ milk under constant temperature (25°C) and impeller speed (100 rpm) for a propagation time of 24 h. Several mathematical models proposed to predict the pH value and kefir grain biomass increase vs propagation time were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…By adding 0.25 g/L Mn2+ and Mg2+, the amount of biomass at the end of propagation time was 30.33 g/L (growth rate was 60.62%), higher than when using carbon source. Demirhan et al (2011) also found that the kefir biomass was the highest when added MgO, containing 0.30 g⁄L with 46.3% increase.…”
Section: Influence Of Different Nutrients Added To the Culture Mediummentioning
confidence: 74%
“…By adding 0.25 g/L Mn2+ and Mg2+, the amount of biomass at the end of propagation time was 30.33 g/L (growth rate was 60.62%), higher than when using carbon source. Demirhan et al (2011) also found that the kefir biomass was the highest when added MgO, containing 0.30 g⁄L with 46.3% increase.…”
Section: Influence Of Different Nutrients Added To the Culture Mediummentioning
confidence: 74%
“…Likewise, the authors modeled the behavior of kefir using the Richards model, reaching the highest values of the coefficient of determination and low values of the standard error. Demirhan et al (2011) and Apar et al (2017) obtained an adjusted R 2 between 0.96 and 0.99 for the same model, evaluating both different operating conditions and culture media for the consortium; unlike this study that achieved an R 2 of 0.305 for this reason, it was not included for B in the analysis of the Richards model. The t L predicted for B by the Gompertz and Logistic models ranged from 16.32 to 17.26 h, with μ max of 0.0257 and 0.0266, respectively.…”
Section: Resultsmentioning
confidence: 61%
“…The experimental data were fitted to the Logistic, Gompertz, and Richards models (E Demirhan et al, 2011; Tramšek & Goršek, 2008) to describe the biomass increase in the three kefir strains. The model that best described the behavior of the experimental data was selected as the one with the highest coefficient of determination R 2 and the lowest chi‐square value (χ 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the same authors studied the effect of MgO, MgSO 4 × 7H 2 O, ZnSO 4 × 7H 2 O, CaSO 4 × 1/2H 2 O, and Fe 2 O 3 introduction into milk with kefir grains. MgO had the greatest effect on growth, increasing the kefir grains’ biomass by 46.3%, and Fe 2 O 3 was the only supplement that did not show any effect [ 141 ].…”
Section: Other Supplementsmentioning
confidence: 99%